MODERN APPROACHES TO DIAGNOSTICS OF MICROCIRCULATION DISTURBANCES IN GYNECOLOGICAL PRACTICE (A LITERATURE REVIEW) - M. M. Damirov; O. B. Shakhova; Z. I. Sattarova; O. N. Oleynikova (Неотложная медицинская помощь)
The study of microcirculation is one of the most growing diagnostic areas. The article summarizes the literature on microcirculation disorders in gynecological patients. Modern methods of microcirculation disorders diagnostics have been analyzed. We also described techniques of laser Doppler fl owmetry (LDF) to assess changes in local microcirculation of the pelvic organs. The results of the clinical use of this technique in patients with various gynecological diseases are reported.